An illustrated Chinese materia medica - Wu, Jing-Nuan, 1933- (OUP E-Books., 2005)
Herbal medicine, one of the cornerstones of traditional Chinese medicine, has evolved over centuries of clinical practice and results in a vast body of knowledge encompassing more than 6,000 substances, most of whose effects and uses have been documented and researched. This beautifully "Illustrated Chinese Materia Medica" offers contemporary medicinal, pharmaceutical, natural product chemists as well as practitioners of homeopathic and alternative medicines authentic, concise information on the 320 herbs used in 80 per cent of medicinal formulations in traditional Chinese medical practice. It also provides an overview of traditional Chinese medicine as a framework for understanding how herbal medicines fit within an integrated approach to health and well-being